Human macrophage polarization shapes B. pertussis intracellular persistence. Issue 1 (23rd November 2021) - Valdez, Hugo A; Marin Franco, Jose L; Gorgojo, Juan P; Alvarez Hayes, Jimena; Balboa, Luciana; Fernandez Lahore, Marcelo; Sasiain, María C; Rodriguez, Maria Eugenia
Abstract: We previously demonstrated that Bordetella pertussis, the etiologic agent of whooping cough, is able to survive inside human macrophages. The aim of this study was to examine the influence of macrophage polarization in the development of B. pertussis intracellular infections. To this end, primary human monocytes were differentiated into M1, M2a, or M2c macrophages and further infected with B. pertussis . Infected M1 macrophages showed a proinflammatory response evidenced by the production of TNF-α, IL-12p70, and IL-6. Conversely, infection of M2a and M2c macrophages did not induce TNF-α, IL-12p70, nor IL-6 at any time postinfection but showed a significant increase of M2 markers, such as CD206, CD163, and CD209. Interestingly, anti-inflammatory cytokines, like IL-10 and TGF-β, were induced after infection in the 3 macrophage phenotypes. B. pertussis phagocytosis by M1 macrophages was lower than by M2 phenotypes, which may be ascribed to differences in the expression level of B. pertussis docking molecules on the surface of the different phenotypes. Intracellular bactericidal activity was found to be significantly higher in M1 than in M2a or M2c cells, but live bacteria were still detected within the 3 phenotypes at the late time points after infection. In summary, this study shows that intracellular B. pertussis is able to survive regardless of the macrophage activation program, but its intracellular survival proved higher in M2 compared with the M1 macrophages, being M2c the best candidate to develop into a niche of persistence for B. pertussis . Graphical Abstract: B. pertussis is able to survive within both M1 and M2 macrophages but M2c proved to be the best suited subtype for bacterial intracellular persistence.